Consultation skills for the MRCGP - Naidoo, P. (Prashini) (Scion Publishing Limited, 2017)
This book helps readers pull together the knowledge and communication skills required for success in the consultation components of the MRCGP exam, namely Clinical Skills Assessment (CSA) and Clinical Observation Tool (COT)."--Back cover